Maraviroc decreases CCL8-mediated migration of CCR5+ regulatory T cells and reduces metastatic tumor growth in the lungs. (2nd June 2016) - Halvorsen, E. C.; Hamilton, M. J.; Young, A.; Wadsworth, B. J.; LePard, N. E.; Lee, H. N.; Firmino, N.; Collier, J. L.; Bennewith, K. L.
ABSTRACT: Regulatory T cells (Tregs) play a crucial physiological role in the regulation of immune homeostasis, although recent data suggest Tregs can contribute to primary tumor growth by suppressing antitumor immune responses. Tregs may also influence the development of tumor metastases, although there is a paucity of information regarding the phenotype and function of Tregs in metastatic target organs. Herein, we demonstrate that orthotopically implanted metastatic mammary tumors induce significant Treg accumulation in the lungs, which is a site of mammary tumor metastasis. Tregs in the primary tumor and metastatic lungs express high levels of C–C chemokine receptor type 5 (CCR5) relative to Tregs in the mammary fat pad and lungs of tumor-free mice, and Tregs in the metastatic lungs are enriched for CCR5 expression in comparison to other immune cell populations. We also identify that C–C chemokine ligand 8 (CCL8), an endogenous ligand of CCR5, is produced by F4/80 + macrophages in the lungs of mice with metastatic primary tumors. Migration of Tregs toward CCL8 ex vivo is reduced in the presence of the CCR5 inhibitor Maraviroc. Importantly, treatment of mice with Maraviroc (MVC) reduces the level of CCR5 + Tregs and metastatic tumor burden in the lungs. This work provides evidence of a CCL8/CCR5 signaling axis driving Treg recruitment to the lungs of mice bearing metastatic primary tumors, representing a potential therapeutic target to decrease Treg accumulation and metastatic tumor growth.